Investigation of LEPS potential energy surface for the interaction of a Pt(111) surface with a hydrogen atom - VURDU, Can Doğan (Balikesir Universitesi Fen Bilimleri Enstitusu Dergisi, 2018)
In this work, the identification of a potential energy surface between H atom and Pt(111) surface has been studied through the use of London-Eyring-Polanyi-Sato potential energy function (PEF).  The energy values for the H–Pt(111) interaction calculated using density functional theory were used to determine the parameters of this PEF by using a nonlinear least-squares method.  For this study, four symmetric sites on the surface were considered as a top site, bridge site, fcc-hollow site and hcp hollow site.  It can be determined which sites on the Pt surface are penetration region, adsorption site or scattering site by defining the potential energy surface.  It is found that both of the hollow sites of the surface are regions where H atom can penetrate directly to subsurface and it can be held easily on the surface.
Keywords: Potential energy surface; LEPS; Pt(111) surface; adsorption; Potansiyel enerji yüzeyi; LEPS; Pt(111) yüzeyi; adsorpsiyon